The use of mathematical formulas to control river pollution Study area Diyala River within the city of Baquba (Journal of Planner and Development, 2008)
Pollution of the aquatic environment and the depletion of the natural resource cause imbalance in the natural balance of the river environment and contributes to the deterioration of life and the killing of living organisms. Most of the old and modern cities and urban centers were set up close to the rivers because water enters the main lifeblood and all its facilities. The proximity of cities to rivers caused environmental problems resulting from the dumping of residues of these cities to a large and continuous, these wastes include all uses of the city (industrial, agricultural, residential and commercial) and others. The accumulation of these wastes inside the rivers water kills life and makes them unsuitable for various uses to bury them, not clean them and not clean them, and their use for any use may cause health and economic problems. Therefore, it is necessary to work hard to protect the rivers from pollution and protect them. Sports laws and formulas, and we are here to address mathematical formulas and their role in the identification and control of river pollution. In general, mathematical formulas are one of the main ways to control the pollution of rivers, but not alone, but using the rest of the roads, this control is done because the role of the main formulas lies in the discovery of pollution and its degree in the rivers..